THE READINESS OF IMPLEMENTING THE HR DIGITALIZATION SYSTEM USING HUMAN CAPITAL MANAGEMENT MATURITY AND ORGANIZATIONAL AGILITY METHOD (CASE STUDY AT PT. PIN) (The Indonesian Journal of Business Administration, 2019)
In response to fluctuate in net income in the post and courier business growth projections - which supports over 55% of PT. PIN's revenue, and the positive high growth projection of e-commerce businesses by ten times and package business revenues and PT. PIN couriers decided to divert business to digital. To become a successful postal and courier company, PT. PIN created a strategic initiative with HR transformation that adopted the concept of digitalization system by considering the success factors of implementing the HR digitization system for that success. This paper aims to evaluate the implementation of strategic human resource management initiatives based on digitalization systems - the successful implementation of HR digitalization transformation, through HR Maturity and the Organizational Agility Maturity model and formulate recommendations for PT. PIN to make organizations more mature and agile. This study uses 11 dimensions of the HR Maturity Model Method and Organizational Agility as a tool. The questionnaire consisted of 2 methods, 8 dimensions, 29 indicators and 42 questions asking about the extent to which respondents agreed with the practice of the current conditions in accordance with the questions asked. The survey results indicate that PT. PIN is currently in a state of underdeveloped HR organization or at level three where the company still performs basic HR and agile functions as an organization. These results conclude that with the method used in this study, transformation can be declared less successful. This is because according to the results there are gaps in the capabilities that the organization has now with the capabilities needed in the future, such as maintaining and improving workforce optimization still need improvement and dexterity is currently still needed, especially the increase related to flexible structure.Keywords:Human Resource Management, Organizational Agility, HCM Maturity, Transformation